2015
DOI: 10.1038/srep11698
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene glaciations, demographic expansion and subsequent isolation promoted morphological heterogeneity: A phylogeographic study of the alpine Rosa sericea complex (Rosaceae)

Abstract: While most temperate plants probably underwent glacial constriction to refugia and interglacial expansion, another type of interglacial refugia might have existed to maintain alpine plants during warm periods. To test this hypothesis, we applied phylogeographic methods to 763 individuals (62 populations) which belong to 7 taxonomically difficult species of the Rosa sericea complex distributed in alpine regions of the temperate and subtropical zones in eastern Asia. We used three chloroplast (cp) DNA fragments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 65 publications
4
43
0
1
Order By: Relevance
“…Phylogeographic Structure and Inference of Demographic Patterns -Our results on the phylogeographic structure of R. dauricum were consistent with previous studies of temperate montane flora in northeastern China, which were strongly structured phylogeographically (Chen et al 2008;Tian et al 2009;Chen et al 2012b). In this study, N ST was significantly …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Phylogeographic Structure and Inference of Demographic Patterns -Our results on the phylogeographic structure of R. dauricum were consistent with previous studies of temperate montane flora in northeastern China, which were strongly structured phylogeographically (Chen et al 2008;Tian et al 2009;Chen et al 2012b). In this study, N ST was significantly …”
Section: Discussionsupporting
confidence: 81%
“…When confronted with chloroplast marker choice in Rhododendron, Ericaceae, or other related families, these six primer pairs and associated chloroplast regions may be priorities. From the sequences amplified by those primer pairs, our results showed that the haplotype diversity (H d = 0.834) of R. dauricum was higher than that of other temperate shrub or small-sized tree species, such as R. delavayi ( Gao et al 2015), and it was also higher than the mean for cpDNA as reported by Petit et al (2005) in 170 species of angiosperms (H d = 0.670).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The East Asian mainland differs from Europe and North America by having remained largely unglaciated during the Pleistocene (Feng, Mao, Sandel, Swenson, & Svenning, ; Hewitt, ; Li, Shu, Zhou, Zhao, & Zhang, ). Relevant studies in this region are rare and have primarily focused on southwestern China and adjacent areas with their complex topography and high mountains, such as the Himalayas (e.g., Gao, Zhang, Gao, & Zhu, ; He & Jiang, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to study the population expansion of trees as their life span is very long, but still there are methods like radiocarbon dating which solve this problem to some extent are available (Bennett, 1983). Researchers studied population expansion and successive isolation stimulated morphological heterogeneity in Rosa sericea complex (Gao, Zhang, Gao, & Zhu, 2015). They studied three chloroplast DNA fragments such as ndhJ-trnF, trnL-trnF and ndhF-rpl32 and nuclear microsatellite to confirm whether cold tolerant plants accomplished expansion during the Pleistocene.…”
Section: Population Expansionmentioning
confidence: 99%